PENDEKATAN REGRESI NONPARAMETRIK SPLINE UNTUK PEMODELAN INDEKS PEMBANGUNAN MANUSIA DI PULAU KALIMANTAN - Kethy Valentina Permatasari; Fuad Muhajirin Farid; Thina Anggraini - (Universitas Lambung Mangkurat, 2022)
The Human Development Index is a number that measures the achievement of human development based on a number of basic components of quality of life that can affect the level of productivity produced by a person. The calculation of the human development index can be based on three dimensions, namely the health dimension, the education dimension, the standard of living dimension In this study the method used is nonparametric spline regression. This nonparametric spline regression method is used to obtain the estimated regression curve through the data fitting approach. This method is also very suitable for use with data that changes frequently and does not determine a certain pattern. Spline is a model that has statistical and visual interpretation and has a very good ability to be generalized to complex and complex statistical models. The purpose of this study is to explain how the influence and how the best model of the number of health facilities, number of school facilities, economic growth, labor force participation rate and open unemployment rate on the human development index on the island of Kalimantan using nonparametric spline regression. The results of this study are the best model is at one knot point and the number of health facilities, the number of school facilities, economic growth, labor force participation rates and the open unemployment rate affect the dependent variable by 42.98 percent or can be said to be low, while the rest is explained by the variable others that are not included in the model.